Effects of Allium mongolicum Regel ethanol extract on three flavor-related rumen branched-chain fatty acids, rumen fermentation and rumen bacteria in lambs - Zhao, Yabo; Zhang, Yanmei; Khas, Erdene; Ao, Changjin; Bai, Chen (Frontiers in Microbiology, 2022)
The objective of this study was to evaluate the effect of Allium mongolicum Regel ethanol extract (AME) on the concentration of three branched-chain fatty acids (BCFAs) related to flavour, fermentation parameters and the bacteria and their correlations in the rumen of lambs. A total of thirty 3-month-old male, Small-tailed Han sheep (33.60 ± 1.23 kg) were randomly distributed into 2 groups as follows: control group ( CON) was fed a basal diet and AME group was fed a basal diet supplemented with 2.8 g·lamb-1·d-1 A. mongolicum Regel ethanol extract. AME supplementation decreased (P = 0.022) 4-methyloctanoic acid (MOA) content and tended to lower (P = 0.055) 4-methylnonanoic acid (MNA) content in the rumen. Compared to CON group, the ruminal concentrations of valerate and isovalerate were higher (P = 0.046 and P = 0.024, respectively), and propionate was lower (P = 0.020) in the AME group. At the phylum level, the AME group had a lower abundance of Bacteroidetes (P = 0.014) and a higher abundance of Firmicutes (P = 0.020) than the CON group. At the genus level, the relative abundances of Prevotella (P = 0.001), Christensenellaceae_R-7_group (P = 0.003), Succiniclasticum (P = 0.004) and Selenomonas (P = 0.001) were significantly lower in the AME group than in the CON group, while the relative abundances of Ruminococcus (P < 0.001), Quinella (P = 0.013), and Lachnospiraceae_XPB1014_group (P = 0.001) were significantly higher. The relative abundances of Prevotella (P = 0.029, R = 0.685; P = 0.009, R = 0.770), Christensenellaceae_R-7_group (P = 0.019, R = 0.721; P = 0.029, R = 0.685) and Succiniclasticum (P = 0.002, R = 0.842; P = 0.001, R = 0.879) was positively correlated with MOA and MNA levels, and the relative abundance of Lachnospiraceae_XPB1014_group (P = 0.033, R = -0.673) was negatively correlated with MOA. The relative abundance of Christensenellaceae_R-7_group (P = 0.014, R = -0.744) and Prevotellaceae_UCG-003 (P = 0.023, R = -0.706) correlated negatively with the EOA content. In conclusion, these findings suggest that the AME affected the concentration of BCFAs, fermentation parameters and the rumen bacteria in the rumen of lambs.